1974
DOI: 10.1111/j.1440-1754.1974.tb01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Response to Cystic Fibrosis

Abstract: SYNOPSIS The effects of cystic fibrosis on 50 Victorian families with one or more affected children were examined in a study carried out between August 1972 and February 1973. The social and emotional problems experienced by family members, particularly the patients and mothers, are reported on. At all ages, socially embarrassing symptoms and awareness of being different create major problems for the patient. The uncertainty of prognosis and doubts about the prospects of employment are specially relevant for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Any differences from peers can be particularly distressing to an adolescent and could contribute to the development of anxiety and depression. CF affects almost all body systems and produces a wide range of symptoms that patients may find very embarrassing and distressing [14, 15]. An Australian survey found that symptoms seen commonly in CF (coughing, flatulence, steatorrhoea, discoloured teeth from antibiotics, and digital clubbing) were extremely distressing and isolating for adolescents, especially those that cause visible difference to their peers (pubertal delay, short stature, and low body mass) [15].…”
Section: Puberty and Body Imagementioning
confidence: 99%
“…Any differences from peers can be particularly distressing to an adolescent and could contribute to the development of anxiety and depression. CF affects almost all body systems and produces a wide range of symptoms that patients may find very embarrassing and distressing [14, 15]. An Australian survey found that symptoms seen commonly in CF (coughing, flatulence, steatorrhoea, discoloured teeth from antibiotics, and digital clubbing) were extremely distressing and isolating for adolescents, especially those that cause visible difference to their peers (pubertal delay, short stature, and low body mass) [15].…”
Section: Puberty and Body Imagementioning
confidence: 99%
“…Subsequent studies of children with CF and their families have further confirmed that the chronic stress of this life-threatening illness has psycho-social implications (10,11). Allen et al (2) in 1974 discussed marital discord, maternal overprotectiveness, economic stress, and extreme sibling rivalry in the families of 50 Australian children with cystic fibrosis. Falkman (3) in Sweden, from interviews and questionnaires, found the children with CF to have sleep difficulties, enuresis, and isolation from their peers.…”
mentioning
confidence: 89%
“…The past 20 years have brought increasingly sophisticated medical treatment for cystic fibrosis (CF), with emphasis on aggressively persuing earlier diagnosis and more vigorous supportive treatment (1)(2)(3)(4)(5). In 1984, Matthews & Drotar (6) reported that by 1981, '50% of children with CF were living into their 20's'.…”
mentioning
confidence: 98%
“…These stressors often result in decreased marital communication and increased conflict. Siblings also struggle with issues such as survivor guilt and resentment of the attention and resources allocated to the CF child (Allan et al, 1974;McCollum & Gibson, 1970;McCrae, Cull, Burton, & Dodge, 1973).…”
mentioning
confidence: 95%
“…Reality stressors include the burdens of an intense daily management regimen of chest physiotherapy, diet, and medications; inability to obtain even routine child care (much less respite care); financial burdens from the cost of treatment; lack of mobility in parental occupations and careers due to their child's uninsurability; and social ostracism as a response from family and friends (Allan, Townley, & Phelan, 1974;Anderson, 1960;McCollum & Gibson, 1970). Psychological stressors include a process of anticipatory grief associated with a chronic but eventually fatal illness; guilt, fear, and displaced anger associated with the genetic nature of the illness; and the often unacceptable resentment of the physical and psychological burdens inherent in caring for the child.…”
mentioning
confidence: 99%